2011
DOI: 10.1200/jco.2011.29.15_suppl.3533
|View full text |Cite
|
Sign up to set email alerts
|

The association of alternate VEGF ligands with resistance to anti-VEGF therapy in metastatic colorectal cancer.

Abstract: Background: Circulating angiogenic factors are altered in patients with mCRC receiving bevacizumab. Evaluation of alterations in levels of VEGF ligands may provide insights into possible resistance mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…98 Of interest, VEGFC has been associated to both innate and acquired resistance to bevacizumab, and should be noted again that in our analysis VEGFR2-targeting ramucirumab appears to perform better than bevacizumab. 99 Consistently with these results, TKIs that mainly target VEGFR2 signaling, such as apatinib, showed the better results in term of OS. Considering the role played by the VEGFR2/ VEGFR3 axis in inflammation, immunology, and angiogenesis these agents seems to be promising and warrant further investigation in aGC.…”
Section: Discussionsupporting
confidence: 76%
“…98 Of interest, VEGFC has been associated to both innate and acquired resistance to bevacizumab, and should be noted again that in our analysis VEGFR2-targeting ramucirumab appears to perform better than bevacizumab. 99 Consistently with these results, TKIs that mainly target VEGFR2 signaling, such as apatinib, showed the better results in term of OS. Considering the role played by the VEGFR2/ VEGFR3 axis in inflammation, immunology, and angiogenesis these agents seems to be promising and warrant further investigation in aGC.…”
Section: Discussionsupporting
confidence: 76%
“…In particular, circulating levels of PlGF,SDF-1 and MCP-3 (the latter two factors are known to be potent chemoattractants for myeloid cells and hematopoietic progenitor cells) increased during treatment with bevacizumab in progressing patients [11]. The elevation of circulating PlGF levels in patients progressing during bevacizumab containing regimen was further confirmed in a retrospective study enrolling a total of 450 patients [12] and suggested in another study [13].…”
Section: Predictive Markerssupporting
confidence: 51%
“…Interestingly, immunohistochemistry analyses of archived formalin-fixed, paraffin-embedded tumor samples from the phase III MAX trial in metastatic colorectal cancer identified VEGF-D expression as a candidate marker of resistance to bevacizumab (Weickhardt et al 2011). VEGF-D was also independently implicated in a modestsized non-randomized study in patients with metastatic colorectal cancer conducted by Lieu et al (2011); these investigators found that plasma VEGF-D levels as well as VEGF-C rose in the setting of disease progression.…”
Section: Biomarkersmentioning
confidence: 99%
“…For the VEGF inhibitor pazopanib, using data from the phase III study of pazopanib versus best supportive care, Lieu et al (2011) analyzed seven angiogenic factors previously suggested to predict benefit from pazopanib in non-randomized studies. Circulating baseline IL6, IL8, HGF, OPN, TIMP1, and VEGF correlated with baseline tumor burden, whereas higher levels of IL6, HGF, and OPN were associated with lesser tumor responses to treatment with pazopanib (Liu et al 2011).…”
Section: Biomarkersmentioning
confidence: 99%